“And since the Italians are always one step ahead of us, and of everyone…” Italian Thought Between Ontological Weakness and Governmentality - Fabbri, Lorenzo (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
It is March 8th 1978, and Michel Foucault is entering the second half of his lesson on governmentality at the Collège de France. The room is packed as usual. And towards the end of the session, Foucault – half-joking – claims: Italians were the first to formalize the difference between law and police, because they are always one step ahead of anyone. In this essay, Lorenzo Fabbri takes at face value Foucault’s remark and shows how it is the discovery of life that in the 16th century propelled, and still propels today, Italian thought ahead of its times.